2005
DOI: 10.1007/s10443-005-2730-x
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Composite Steel Bridges Using GFRP Plates

Abstract: The current study is a part of an extensive research program conducted to assess the use of Glass Fibre Reinforced Plastic (GFRP) sheets in enhancing the flexural capacity of steel beams. The properties of a heavy-duty adhesive system that can be used to bond GFRP sheets to the flanges of steel beams were experimentally determined in a previous study. The excellent performance of a W-shaped steel beam strengthened using GFRP sheets has encouraged the authors to assess the applicability of this technique to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In this study composite concrete-steel bridge girders were strengthened using GFRP with tensile strength of 207 MPa and a modulus of elasticity of 17 GPa. It was concluded that a 25% increase in truckload can be achieved using the described system without any reported premature failure in the concrete slab, GFRP or adhesive [6].…”
Section: Introductionmentioning
confidence: 92%
“…In this study composite concrete-steel bridge girders were strengthened using GFRP with tensile strength of 207 MPa and a modulus of elasticity of 17 GPa. It was concluded that a 25% increase in truckload can be achieved using the described system without any reported premature failure in the concrete slab, GFRP or adhesive [6].…”
Section: Introductionmentioning
confidence: 92%
“…It is commonly used for structural reinforcement, rehabilitation, and retrofitting of concrete structures such as bridges, beams, and columns [5]. Pultruded GFRP also finds applications in the construction of underground structures such as pipelines and storage tanks [6].…”
Section: Introductionmentioning
confidence: 99%